CHANGES IN CALPROTECTIN LEVEL, ITS RELATIONSHIP TO THE CLINICAL AND LABORATORY PARAMETERS OF DISEASE ACTIVITY AND SIGNIFICANCE FOR PREDICTING THE THERAPEUTIC RESPONSE IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH ETANERCEPT - A. O. Pchelintseva; A. P. Zhornyak; N. G. Ionichenok; E. Yu. Panasyuk; A. E. Ilyina; I. A. Andrianova; E. E. Gubar; E. S. Tsvetkova; M. V. Cherkasova; E. N. Aleksandrova; L. N. Denisov; E. L. Nasonov (Научно-практическая ревматология)
Objective: to analyze changes of serum calprotectin (CP) concentration, its relationship to the clinical and laboratory parameters of rheumatoid arthritis (RA) activity, and the significance of baseline CP level for predicting therapeutic response in RA patients treated with etanercept (ETC).Subjects and methods. A total of 84 patients with moderate and high RA activity (mean DAS28 6.35±0.92) who had been ineffectively treated with disease-modifying antirheumatic drugs were examined. The patients received ETC 50 mg/week subcutaneously for 34 weeks. To assess RA activity, tender and swollen joint count, pain, patient’s and physician’s assessment of global disease activity on 100-mm visual analogue scale and DAS28 were used. Functional status was evaluated by HAQ and RAPID3. Treatment efficacy was assessed according to the European League against Rheumatism (EULAR) criteria and the American College of Rheumatology (ACR) criteria. Serum concentration of CP was tested before, 12 and 25 weeks after start of therapy.Results and discussion. There was a statistically significant (p < 0.0001) decrease in CP concentrations after 12 weeks of ETC therapy. Later (after 25 weeks) CP level remained essentially unchanged. CP concentration correlated with erythrocyte sedimentation rate, C-reactive protein level, swollen joint count, and DAS28. Baseline CP level was not a predictor for achieving the therapeutic response according to the EULAR and ACR criteria. In a group of patients unresponsive to treatment according to the EULAR criteria, CP levelrose at 25 weeks whereas it fell during clinical improvement. In the patients achieving ACR 50 and 70% response, changes of CP level were significantly better than those in the other patients.Conclusion. ETC therapy caused a considerable reduction of CP level, clinical and laboratory parameters of RA activity. The baseline concentration of CP was not a predictor for achieving the response to ETC treatment.